Efficacy and safety analysis of non-radical surgery for early-stage cervical cancer (IA2 IB1): a systematic review and meta-analysis - Zeng, Siyuan; Xiao, Simin; Xu, Yang; Yang, Ping; Hu, Chenming; Jin, Xianyu; Liu, Lifeng (Frontiers in Medicine, 2024)
Objective Radical hysterectomy has long been considered as the standard surgical treatment for early-stage cervical cancer (IA2 to IB1 stages), according to the 2009 International Federation of Obstetrics and Gynecology. This study aims to conduct an in-depth evaluation of the effectiveness and safety of non-radical surgery as an alternative treatment for patients with early-stage cervical cancer. Methods A systematic search of online databases including PubMed, Embase, and the Cochrane Library was conducted to identify relevant literature on surgical treatment options for early-stage cervical cancer. Keywords such as “cervical cancer,” “conservative surgery,” “early-stage,” “less radical surgery,” and “simple hysterectomy” were used. Meta-analysis was performed using Stata 15.0 software, which included randomized controlled trials (RCTs) and cohort studies. Results This meta-analysis included 8 eligible articles covering 9 studies, with 3,950 patients in the simple hysterectomy (SH) surgery group and 6,271 patients in the radical hysterectomy (RH) surgery group. The results indicate that there was no significant difference between the two groups in terms of the Overall Survival (OS) (HR = 1.04, 95% CI: 0.86–1.27, p = 0.671; Heterogeneity: I2 = 33.8%, p = 0.170), Disease Free Survival (DFS) (HR = 1.39, 95% CI: 0.59–3.29, p = 0.456; Heterogeneity: I2 = 0.0%, p = 0.374), Cervical Cancer Specific Survival (CCSS) (HR = 1.11, 95% CI: 0.80–1.54, p = 0.519; Heterogeneity: I2 = 11.9%, p = 0.287) and recurrence rate (RR = 1.16, 95% CI: 0.69–1.97, p = 0.583; Heterogeneity: I = 0.0%, p = 0.488). However, the mortality rate (RR = 1.35, 95% CI: 1.10–1.67, p = 0.006; Heterogeneity: I2 = 35.4%, p = 0.158) and the rate of postoperative adjuvant therapy (RR = 1.59, 95% CI: 1.16–2.19, p = 0.004; Heterogeneity: I2 = 92.7%, p < 0.10) were higher in the SH group compared to those in the RH group. On the other hand, the incidence of surgical complications was lower in the SH group (RR = 0.36, 95% CI: 0.21–0.59, p = 0.004; Heterogeneity: I2 = 0.0%, p = 0.857) than that in the RH group. Subgroup analysis revealed that patients in the IB1 stage SH group had a significantly higher mortality rate compared to those in the RH group (RR = 1.59, 95% CI: 1.23–2.07, p < 0.001; Heterogeneity: I2 = 0.0%, p = 0.332). However, there was no significant difference in mortality rates between the two groups for patients at stage IA2 (RR = 0.84, 95% CI: 0.54–1.30, p = 0.428; Heterogeneity: I2 = 26.8%, p = 0.243). In the subgroups positive for Lymphovascular Space Invasion (LVSI), patients in the SH group had a significantly higher mortality rate than those in the RH group (RR = 1.34, 95% CI: 1.09–1.65, p = 0.005; Heterogeneity: I2 = 41.6%, p = 0.128). However, in the LVSI-negative subgroups, there was no significant difference in mortality rates between the two groups (RR = 0.33, 95% CI: 0.01–8.04, p = 0.499). Conclusion For patients with early-stage cervical cancer patients at IA2 without LVSI involvement, comparisons between the two groups in terms of OS, DFS, CCSS, recurrence rate, and mortality rates revealed no statistically significant differences, indicating that the choice of surgical approach does not affect long-term survival outcomes for this specific patient group. For patients at IB1 and IA2 stages with LVSI involvement, while there were no significant differences between the two groups in OS, DFS, CSS, and recurrence rate, a significant increase in mortality rates was observed in the SH group. This indicates a potential elevated risk of mortality associated with SH in this subset of patients. Notably, the incidence of surgical complications was significantly lower in the SH group compared to the RH group, highlighting the safety profile of SH in this context. Significantly, among patients in the SH group, an increase in the rate of postoperative adjuvant treatment is associated with a higher occurrence of treatment-related complications. To facilitate more precise patient selection for conservative surgical management, future prospective studies of superior quality are imperative to gain deeper insights into this matter. Systematic review registration PROSPERO (CRD42023451609: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023451609).